Organization design: The continuing influence of information technology - Dibrell,Clay; Miller,T. (Management Decision, 2002)
Drawing from an information processing perspective, this paper examines how information technology (IT) has been a catalyst in the development of new forms of organizational structures. The article draws a historical linkage between the relative stability of an organization's task environment starting after the Second World War to the present environmental instability that now characterizes many industries. Specifically, the authors suggest that advances in IT have enabled managers to adapt existing forms and create new models for organizational design that better fit requirements of an unstable environment. Time has seemingly borne out this hypothesis as the bureaucratic structure evolved to the matrix to the network and now to the emerging shadow structure. IT has gone from a support mechanism to a substitute for organizational structures in the form of the shadow structure. The article suggests that the evolving and expanding role of IT will continue for organizations that face unstable environments.
Keywords: Management; Strategy & Entrepreneurship